Cultural Turns in Aesthetics and Anti-Aesthetics - Perniola, Mario (Filozofski vestnik, 2007)
The paper intends to bridge the existing gap between aesthetic knowledge and contemporary society. The first part focuses on the cultural turn in aesthetics, the roots of which can already be found in the English criticism of the eighteenth century. This enterprise is inspired by a methodology that regards aesthetics as a "meeting place" of many disciplines and varying cultural traditions. A second type of cultural turn is carried out by writers (e.g. Baudelaire): the target of their polemic is the concept of aesthetic disinterestedness. According to them, the beautiful, instead, has to create the greatest interest because it is none other than the promise of happiness. However, the two different approaches are not so incompatible as seems at first sight. Finally, the text focuses on the New Age and the culture of performance, which, even if presenting opposite traits, have one thing in common: they translate at the empirical and factual level experiences that originally belonged to another sphere, namely the spiritual and the symbolic.